When Love Hurts: The Hidden Psychological Damage of Toxic Relationships Leading to Suicide Ideation in Early Adult Women - Suparmi, Dhita; Hanifah, Fikrotul (Psikostudia : Jurnal Psikologi, 2026)
The phenomenon of toxic relationships in Indonesia indicates the existence of unhealthy relationship patterns that cause prolonged psychological stress. This study aims to examine the relationship between toxic relationships and suicide ideation in young adult women. This research uses a quantitative approach and employs a Pearson product-moment correlation analysis model with a sample of 251 participants. Data collection was carried out using the toxic relationship instrument and the Beck Scale for Suicide (BSS). The research results indicate a positive relationship between toxic relationships and suicide ideation; the higher the level of toxic relationships experienced by an individual, the higher the likelihood of suicidal thoughts. This research provides an understanding that the dynamics of toxic relationships can be a significant predictor of the emergence of suicidal ideation in young adult women.Fenomena toxic relationship di Indonesia menunjukan adanya pola hubungan tidak sehat yang menimbulkan tekanan psikologis yang berkepanjangan. Penelitian ini ditujukan untuk melihat hubungan antara toxic relationship dengan suicide ideation pada wanita dewasa awal. Penelitian ini menggunakan pendekatan dengan metode kuantitatif dan menggunakan model analisis korelasi product moment dengan 251 sampel. Pengumpulan data dilakukan memakai instrumen toxic relationship dan Beck Scale for Suicide (BSS). Hasil penelitian menyatakan terdapat hubungan positif yang signifikan antara toxic relationship terhadap suicide ideation, semakin tinggi tingkat toxic relationship yang dialami individu maka semakin tinggi kecenderungan munculnya ide bunuh diri. Penelitian ini memberikan pemahaman bahwa dinamika toxic relationship dapat menjadi prediktor yang signifikan terhadap munculnya ide bunuh diri pada wanita dewasa awal.